Pendekatan Hukum Preventif dalam Pencegahan Korupsi di Aceh - Munawir, Munawir; Salsabila, Almas; Hidayati, Raudhatul (Al-Mizan, 2024)
Corruption is a major issue hindering development in many regions of Indonesia, including Aceh. As a region implementing Sharia Law, Aceh has a unique potential to integrate religious values into legal approaches to prevent corruption. This study aims to analyze how preventive legal approaches based on Sharia Law can be effectively implemented to combat corruption in Aceh. Using a qualitative method with a descriptive-analytical approach, data were collected through in-depth interviews, field observations, and document analysis. The study found that preventive legal approaches in Aceh face challenges, such as weak internal supervision and insufficient regulatory dissemination. However, integrating Sharia values with preventive legal strategies shows significant potential to create a transparent and accountable governance system. Regulations like Qanun need optimization through strict supervision and modern technological support. The study concludes that strengthening the capacity of law enforcement, involving religious leaders, and promoting legal awareness education are crucial for the success of this approach. This research contributes by offering a corruption prevention strategy that adapts to Aceh’s local characteristics and could serve as a model for other regions.